The effects of early rehabilitation on functional exercise tolerance in decompensated heart failure patients: results of a multicenter randomized controlled trial (ERIC-HF study) - Delgado, Bruno (2022)
To analyze (1) the effect of an aerobic training program on functional exercise tolerance in decompensated heart failure (DHF) patients; (2) to assess the effects of an aerobic training program on functional independence; and (3) dyspnea during activities of daily living. Design A randomized controlled clinical trial with follow-up at discharge. Settings Eight hospitals. Recruitment took place between 9/ 2017 and 3/2019. Group Assignments Patients with DHF who were admitted to the hospital, were randomly assigned to usual rehabilitation care guideline recommended (control group) or aerobic training program (exercise group). Main outcome Functional exercise tolerance was measured with a 6-min walking test at discharge. Results In total 257 patients with DHF were included, with a mean age of 67 ± 11 years, 84% (n = 205) had a reduced ejection fraction and the hospital stay was 16 ± 10 days. At discharge, patients in the intervention group walked further compared to the control group (278 ± 117m vs 219 ± 115m, p < 0.01) and this difference stayed significant after correcting for confounders (p < 0.01). A significant difference was found favoring the exercise group in functional independence (96 ± 7 vs 93 ± 12, p = 0.02) and dyspnea associated to ADL (13 ± 5 vs 17 ± 7, p < 0.01) and these differences persisted after correcting for baseline values and confounders (functional independence p < 0.01; dyspnea associated with ADL p = 0.02). Conclusion The ERIC-HF program is safe, feasible, and effective in increasing functional exercise tolerance and functional independence in hospitalized patients admitted due to DHF.